Sintered Cr/Pt and Ni/Au ohmic contacts to B12P2 - Frye, C. D.; Kucheyev, S. O.; Edgar, James H.; Voss, L. F.; Conway, A. M.; Shao, Q. H.; Nikolic, R. J. (My University, 2015)
Icosahedral boron phosphide (B12P2) is a wide-bandgap semiconductor possessing interesting properties such as high hardness, chemical inertness, and the reported ability to self-heal from irradiation by high energy electrons. Here, the authors developed Cr/Pt and Ni/Au ohmic contacts to epitaxially grown B12P2 for materials characterization and electronic device development. Cr/Pt contacts became ohmic after annealing at 700 degrees C for 30 s with a specific contact resistance of 2 x 10(-4) Omega cm(2), as measured by the linear transfer length method. Ni/Au contacts were ohmic prior to any annealing, and their minimum specific contact resistance was similar to l-4 x 10(-4) Omega cm(2) after annealing over the temperature range of 500-800 degrees C. Rutherford backscattering spectrometry revealed a strong reaction and intermixing between Cr/Pt and B12P2 at 700 degrees C and a reaction layer between Ni and B12P2 thinner than similar to 25 nm at 500 degrees C. (C) 2015 American Vacuum Society.
Citation: Frye, C. D., Kucheyev, S. O., Edgar, J. H., Voss, L. F., Conway, A. M., Shao, Q. H., & Nikolic, R. J. (2015). Sintered Cr/Pt and Ni/Au ohmic contacts to B12P2. Journal of Vacuum Science & Technology A, 33(3), 6. doi:10.1116/1.4917010
Keywords: P-Type Gan; Boron-Rich Solids; Electrical-Properties; Phase-Diagram; Growth; Phosphide